Peculiarities of the unit of practical application of correction technology of the students’ physical condition in the process of vocational and applied physical training - Kashuba, Vitaliy; Asauluk, Inna; Dyachenko, Anna (Journal of Education, Health and Sport, 2017)
Relevance. On the basis of analysis and generalization of professional scientific and methodical literature, practical experience of domestic and foreign scientists, it has been established that the low level of physical preparedness of future musicians arises an obstacle to the way of the performing technique improvement, and causes a high degree of need of certain physical qualities devepolement. The research task reflects the gradual achievement of the goal and provided the description of the "practical direction" block features of the correction technology of the physical condition of the students of "Musical Arts"specialty. Research results. In the article, basing on the analysis of scientific methodological literature and own practical experience, the problems of the process of students’ physical training of "Music Art" specialties are formed. The key component of the correction technology of the students’ physical condition is presented – the block of "Practical direction". The main goal of the work within the framework of the "Practical direction" block was chosen the correction of physical preparedness level of students of "Musical Arst" specialty. Conclusions. Implementation of the newest approaches to the planning and organizing of educational and extra-curricular activities on the physical education of students of "Musical Arts" specialty will enhance the efficiency of the process of professional and applied physical training. Prospects for further research will be related to the research of the implementation effectiveness of the correction technology of the physical condition of students of "Musical Arts" specialty as a component of the concept of students’ professional and applied physical training of the creative group of professions.